WEBSITE APPLICATION BY USING BONSAI FLORAGRAHA MACROMEDIA FLASH 8 - Rio Supriyatno Kado; Yulina Yulina.,Skom.,MMSI (Jurnal Sistem Informasi, 2007)
Along with the development of the age and increasingly sophisticated technology, almost all people in the world using the Internet where the Internet provides information of various aspects of the field by means of a container known as a Web site. Website Floragraha this bonsai is a website that contains information about the types of bonsai plants in Indonesia in particular, and may be used as a means of sharing information about types of bonsai plants. Making bonsai Floragraha website uses Flash 8 Macromadia application program, and as the browser is Internet Explorer.